Evaluating the Effectiveness of Teacher-Implemented Video Prompting on an iPod Touch to Teach Food-Preparation Skills to High School Students With Autism Spectrum Disorders. (September 2013) - Johnson, Jesse W.; Blood, Erika; Freeman, Amy; Simmons, Karen
A multiple-probe-across-behaviors design was used to evaluate the effectiveness of video prompts delivered on an iPod Touch to teach food-preparation skills to two high school students with autism spectrum disorders (ASD) and intellectual disability. The special education teacher implemented the procedure in the high school classroom. Student data are interpreted to conclude that video prompting on an iPod Touch was effective in increasing independent performance of both students. The special education teacher was able to implement the procedure with a high degree of fidelity without disrupting the ongoing instructional activities of the classroom. Teacher ratings of the acceptability and perceived effectiveness of the procedures suggested that teacher viewed video prompting on an iPod Touch as a practical, effective, and efficient strategy for teaching food-preparation skills to students with ASD and intellectual disability.